The Use of Animated Videos to Enhance Vocabulary Learning among Elementary School Students - Eza Fadhila; Septa Pertiwi; Kurnia Febianti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study investigates the effectiveness of fruit-themed animated video media in improving English vocabulary mastery among Grade I B students at SD Islam Bunayya. Employing a pre-experimental approach with a One Group Pretest-Posttest Design, this research involved 25 students selected through purposive sampling. Prior to implementation, the vocabulary test instrument underwent a tryout procedure in a separate class to ensure its validity and reliability. Data were analyzed using a paired sample t-test and normalized N-Gain calculations. The findings revealed that the students' mean pretest score of 76.84 increased significantly to 90.44 in the posttest, reflecting a mean gain of 13.60 points. The average N-Gain value was approximately 0.73 (73%), which falls within the high category according to Hake's criteria. The obtained t-count value substantially exceeded the t-table value at the 5% significance level (α = 0.05), leading to the acceptance of the research hypothesis. These results provide strong empirical evidence that fruit-themed animated video media is effective in enhancing English vocabulary mastery among early elementary school students. The implications of this study support the broader integration of visual media technology into English language instruction for young learners in the Indonesian primary school context.